Eksperimen Material Sisa Potongan Kaca Sebagai Panel Dinding Dekoratif - Crecia Mirella; Andereas Pandu Setiawan; Jean Francois Poillot (Intra, 2019)
Glass is a material that often used, which result in increasing amounts of glass waste. The writer want to explore and develop glass waste which actually still has potential economic value but its rarely seen and developed by the people. Thiss research uses the Research and Development method which focuses on material innovation through several stages. The first stage is collecting data, then experimenting with mixing crushed glass waste with some adhesive materials (gypsum, PVAc glue, white cement) and analyzing to produce the final product. The final product in this reserach is decorative wall panels using a mixture of PVAc glue and aggregate of silica sand.